PHYSICAL MOTOR DEVELOPMENT OF 5-6 YEAR OLD CHILDREN IN JAVANESE AND SUNDANESE CULTURES - Nurul Novitasari; cucu soiah; Farah Waheeda Abdul Wahid; Hidjanah Hidjanah; Yulia Nur Annisa; Dyah Kusbiantari; Hastuti Handayani; Mambaun Nikmah; Alfia Rizki Mahmudah; Hawa Solihatul Husna; Hanny Raditya Kumala Sari (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
In Indonesia, two cultural groups that are rich in tradition and have different ethnic backgrounds are the Javanese and the Sundanese. Although both have deep cultural roots, the differences in culture and traditions between these two tribes can have an impact on approaches to childcare in the development of physical motor skills in children aged 5-6 years. Within this framework, this study aims to fill this knowledge gap by conducting a more in-depth and detailed comparison of physical motor development in 5-6 year old children between Javanese and Sundanese cultures. By understanding these differences, this research will hopefully contribute to the development of better educational approaches and interventions that take into account cultural factors in supporting optimal development in children across both cultural groups. This study aimed to compare physical motor development in children aged 5-6 years between Javanese and Sundanese cultures. The type of research used in this study is qualitative research with a descriptive approach, where this descriptive approach is considered appropriate to examine how the actual level of achievement of physical motor development of children aged 5-6 years between Sundanese and Javanese tribes. The research method involved a cross- sectional survey of 107 randomly selected children from two different cultural groups. Data were collected through direct observation and documentation to assess the physical motor skills of 5-6 year old children. The results showed a significant difference in physical motor development between the two different cultural groups of Sundanese and Javanese. Javanese children showed a higher level of physical motor skills compared to Sundanese children, Javanese children had a faster speed compared to Sundanese children.